Analysis Of Problem-Solving Ability Of Numeracy Literacy Questions Based On Personality - Miftahul Khoiri; Dewi Nurmalitasari; Rojiyah Magfiroh (Mathline : Jurnal Matematika dan Pendidikan Matematika, 2025)
This study uses the Polya indicator to analyze numeracy problem-solving abilities based on students' personality types, namely extrovert and introvert. The Polya indicator includes four stages: understanding the problem, planning a solution, implementing the plan, and re-checking the results. This research method uses qualitative data collection techniques such as numeracy literacy problem-solving tests and in-depth interviews. The subjects of the study were 32 students of class VIII D of SMPN 6 Pasuruan, distinguished by their extrovert personality types (18 students) and introvert personality types (14 students), obtained from the results of using the Jung's Type Indicator (JTI) questionnaire. The results showed that students with extrovert personalities tended to use Polya in solving numeracy problems by focusing on the stages of planning solutions and actively implementing plans. They were quicker to take action in implementing plans, although sometimes they required detailed re-checking. Meanwhile, students with introvert personalities were more careful in understanding problems and re-checking the results, but they needed to be quicker in implementing plans. These findings indicate that personality types influence students' approaches in solving numeracy literacy problems.